Effect of different non-feed withdrawal induced moulting methods during moult and post–moult period on the performance of commercial laying hens - SENAPATI, B K; DEHURI, P K; MISHRA, S K; SAMAL, P C; DAS, S K (The Indian Journal of Animal Sciences, 2011)
BV–300 commercial layer birds (144) were randomly distributed into 6 groups having 24 hens in each to study the effect of different non-feed withdrawal induced moulting methods during moult and post-moult period on the performance of commercial laying hens. A complete randomized design was used. Six dietary treatments, viz. T1 (normal diet), T2 (feed withdrawal), T3 (55 g cracked maize+oyster shell grit), T4 (40 g cracked maize+oyster shell grit), T5 (60 g deoiled rice bran+oyster shell grit), and T6 (40 g de-oiled rice bran+oyster shell grit) were tried. Body weight of birds, egg production and feed consumption were recorded during pre-moult, moult and post-moult period. Economics of production was calculated for different periods and for the overall experimental period. Maximum 50% feather shedding was observed in T2 and 30% feather shedding was observed in DORB fed (T5 and T6) groups. The maximum per cent of body weight loss during the moult period was 30.86, 19.12, 18.61, 30.53 and 32.31 within 9, 12, 12, 21 and 21 days for T2, T3, T4, T5 and T6, respectively. Early body weight loss with feather shedding was observed in T2 followed by DORB fed groups. Higher egg production was recorded in moulted groups than that of control and it was highest in T2. During post-moult period, egg production percentage was highest in T2 followed by T6 and T5. Among moulted groups, 40 g cracked maize fed group had the lowest hen-day egg production, which lost the least body weight (18.61%). It is revealed that per cent of body weight loss is directly proportional to the post moult hen-day egg production. The feed efficiency of moulted groups was better than that of control when calculated for the entire period (moult and post-moult period). Among moulted groups, better feed efficiency was observed in feed withdrawal group and DORB fed groups. The moulted groups earned higher profit in comparison to the control. During the post-moult period, the profit was highest in feed withdrawal group in comparison to other moulted groups. But considering both moult and post-moult period, the profit was highest in T6 than that of T2. Based on the above observations, It is revealed that feeding of deoiled rice bran is an effective alternative non-feed withdrawal method on par with the feed withdrawal method of induced moulting.